Modeling of piezoelectric energy harvesting considering the dependence of the rectifier circuit - Clementino, Marcel Araujo; Reginatto, Romeu; Silva, Samuel da [UNESP] (Abcm Brazilian Soc Mechanical Sciences & Engineering, 2014)
Harvesting energy with piezoelectric materials has been a process of many practical applications in structural health monitoring, either to recharge batteries or feed directly sensors and also electronic devices. In general, the amount of energy provided by a vibration source requires converting the alternating current (AC) to direct current (DC) through rectifier circuits before using it as a power supply of electronic devices. However, modeling the harvesting system, usually a PZT sensor bonded on a cantilever beam and coupled to a rectifier circuit, using the same software package is pointed out by some authors as a drawback to overcome, due to its multidisciplinary requirements, involving topics of both mechanical and electrical engineering. In this sense, the goal of the present paper is describe a comprehensive and simple modeling strategy, which considers a single computational platform and accounts for both the electromechanical model of a clamped piezoelectric beam and the practical energy harvesting circuit, seeking further application when optimizing the entire energy harvesting system. Numerical simulations and experimental tests are performed to illustrate the proposed approach, considering a full-wave diode bridge as the non-controlled rectifier circuit and a resistive load, which are directly connected to the cantilevered piezoelectric beam.
Keywords: Energy harvesting; Power electronic; Smart structures; Unified approach